Optimization Strategies and Efficiency Prediction for Silicon Solar Cells with Hybrid Route of PERC and SHJ Passivation Contact - Zixiao Zhou; Qian Kang; Zhaoqing Sun; Yongcai He; Jingjie Li; Lu Wu; Chang Sun; Chaowei Xue; Minghao Qu; Xiaoqing Chen; Zilong Zheng; Bo Wang; et al. (Advanced Science)
Abstract PERC solar cell technology, which emerged in the 1980s, has garnered a substantial portion of the PV market over the past decade. However, the main factors limiting their further efficiency advancements and wider commercialization lie in metal contact recombination and the passivation properties of the functional layers. Despite heterojunction cells demonstrating remarkable efficiency, challenges persist in terms of cost reduction and stability enhancement. This study introduces a novel hybrid solar cell architecture that integrates a diffusion‐free front surface field with a high‐quality heterojunction passivation contact. Through rigorous simulation analysis, it is revealed that the hybrid design surpasses conventional PERC in several key aspects: diminished front‐surface recombination losses, enhanced rear‐contact characteristics, and reduced grid shading. By strategically optimizing the front passivation and adopting single‐side wet etching techniques, a PCE of 24.17% and VOC of 716 mV is successfully achieved on a full‐size commercial czochralski silicon wafer (274.15 cm2). Additionally, both experimental EQE tests and simulations delve into the composition of JSC gain during the optimization process. This comprehensive investigation not only offers an in‐depth assessment of hybrid solar cell performance, but also outlines promising avenues for future optimization aimed at pushing theoretical efficiency limits further and enhancing suitability for large‐scale production.